Naphthylacetic Acid Corn Plant Influence on the Development of the Root System - Nuraliyev Bakhtiyorovich Shukhrat (International Journal on Integrated Education, 2022)
This article discusses the effect of corn on the development of the root system of corn using NAA (naphthalene acetic acid), one of the regulators that affects the maximum yield of plants, increasing their productivity.